César Vallejo: The socio-political commitment of a revolutionary intellectual - Pachas Almeyda, Miguel (2022)
In recent years, interest in the biographical details and poetic production of César Vallejo has increased dramatically, both in Peru and abroad. And this interest is not only in academic circles but among the general readership, including the elderly, adolescents, and children. What aspects of the poet's life catch the attention of readers in the XXI century? What are the most read poems today? How can we explain the validity of his poetic, narrative, essayistic, and theatrical work at a time when the world is living in a post-COVID-19 period? In this research, we will try to answer these questions. And, finally, we will argue why César Vallejo is a universal poet.